Pembuatan Pelet Ikan Bergizi Tinggi untuk Peternak Ikan di Kampung Lampaya dan Weuraya Kecamatan Lhoknga Aceh Besar - Syaubari, Syaubari; Maimun, Teuku; Mukhlishien, Mukhlishien; Djuned, Fauzi M.; Arifin, Riski (Universitas Syiah Kuala, 2024)
The service was carried out in Weuraya Village and Lampaya Village, Lhoknga District, Aceh Besar Regency with the target of fish farmer business groups. At first, the need for fish in Lhoknga and its surroundings only relied on fishing at sea by fishermen. Over time, the need for fish and employment for the community here eventually led to fish farming. Seeing the potential of fish farming that is getting better in this area, a group of people in this area took the initiative to form a fish farming business group located in Lampaya and Weuraya Villages, Lhoknga District, Aceh Besar. These two villages are located not far from the center of the Banda Aceh city market, estimated at about 25 km from the location of the farm which can be reached for approximately 1 hour drive. Determining the composition of fish feed ingredients is an important issue because not all compositions will provide the best results for fish growth. The high price of fish feed in the market with low protein content causes fish farmers to experience difficulties in cultivating fish. The objectives of this activity are first, to concoct their own animal feed from tofu dregs, snails or rice snails, wheat flour, rice bran, and coconut meal which are very widely available around Lhoknga. The second training was for the Lampaya and Weuraya fish farmer groups in Lhoknga sub-district to make fish feed. All members of the Lampaya and Weuraya fish farmer groups are involved in the two scopes of work above, so that these two groups will have the knowledge and skills to make quality and healthy fish feed for fish. From the results of the monitoring of the service team, it is clear that the high enthusiasm of the community can be measured by the crowd of socialization and training participants, as well as the many questions that arise during the practice of making fish pellets. At the end of the activity, the community has mastered how to make their own fish feed and can save 60% of the total cost